1995
DOI: 10.1539/sangyoeisei.37.2_89
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Factors of Low Back Pain among Nursing Aides in Nursing Homes for the Elderly

Abstract: Abstract:Work-Related Factors of Low Back Pain among Nursing Aides in Nursing Homes for the Elderly: Takashi FUJIMURA, at al. Department of Public Health, Kochi Medical School-This survey was performed in December 1991 on 555 nursing aides (NAs) in 32 Special Nursing Homes for the Eld erly (SNHs) in Kochi Prefecture, Japan. The purpose of the survey was to establish the relationship be tween low back pain among NAs in SNHs, and the degree of dependency in the activities of daily living (ADL) of the patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…Statistical associations for MSD are known to include age, duration of employment (28), manual handling (29), work postures, work control, work organisation (1) and patient care needs (1,2). Female gender, smoking and uncomfortable work positions have also been reported as intrinsic risk factors (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical associations for MSD are known to include age, duration of employment (28), manual handling (29), work postures, work control, work organisation (1) and patient care needs (1,2). Female gender, smoking and uncomfortable work positions have also been reported as intrinsic risk factors (30).…”
Section: Discussionmentioning
confidence: 99%
“…Caring for incapacitated, elderly people may be especially hazardous as most nursing home patients depend heavily on nursing care for almost all their daily activities. Studies have shown that the more dependent the patient, the higher the prevalence of musculoskeletal disorders among their caring staff (2). Employment within a nursing home usually involves repetitive work, working fast and expending significant amounts of energy (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, female caregivers have been reported to be at high risk of having high blood pressure [2] and coronary heart disease [3]. Additionally, caregivers have high prevalence rates of low back pain and a high incidence of worker's compensation claims for back injuries [4][5][6]. Low back pain is frequent in various occupations, its presence being related to activities requiring repetitive lifting and repeated activities for which anomalous postures tend to be adopted [7].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of this condition in nursing is high in comparison with that in other occupations and in relation to other types of work [9]. Risk factors include physical workload such as the manual lifting and transferring of patients, working conditions such as working time and rest during the night shift, and the working environment [4]. Among these factors, frequent exposure to the manual lifting and transferring of patients is a widely recognized risk factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation